Persepsi Karyawan Terhadap Penggunaan Artificial Intelligence Pada Instansi Di Kota Semarang - Nindyasari, Nabila Qomara Putri; Kristanto, Rudi Suryo (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The Fourth Industrial Revolution (4IR) is the fourth industrial era since the first industrial revolution in the 18th century. This era is characterized by the emergence of various cutting-edge technologies, including artificial intelligence. There have been changes in human resource management (HRM) in recent years in line with changes in the business world, supported by technological advancements. This research successfully gathered 108 employees who use artificial intelligence working in state-owned or private offices in Semarang City to be used as samples in various analysis tests such as feasibility tests, classical assumption tests, and simple hypothesis analysis tests. The research method is quantitative, using purposive sampling and snowball sampling techniques, conducted by distributing questionnaires, and the results were then processed using SPSS version 26. The results of the study indicate that the artificial intelligence variable has a significant positive influence on employee engagement and artificial intelligence has a significant positive influence onemployee retention.